«Herrer i eget hus» - Finnmarksloven i media - Eira, Stine Sand (Universitetsforlaget / Scandinavian University Press, 2013)
Forholdet mellom samer og nordmenn, og rettigheter til land og vann, ble igjen satt på dagsordenen i Finnmark i forbindelse med debatten om finnmarksloven. En gjennomgang av to finnmarksaviser viser at uenighetene først og fremst handlet om hvorvidt loven førte til privatisering, eller om finnmarkingene nå ble herrer i eget hus. Artikkelen viser at ulike forståelser av likhet, etnisitet og rettferdighet ble brukt retorisk for å vinne fram i diskusjonen om eierrettigheter i Finnmark. In 2005, the Norwegian Parliament passed the Finnmark Act, with ownership of 96 % of Finnmark transferred from the State to the inhabitants of Finnmark. This article discusses the dominant arguments for and against the Act in two local newspapers in Finnmark. The debate was intense. Would the Finnmark Act lead to private ownership based on ethnicity, or equal ownership? Different understandings of equity, justice and ethnicity were used rhetorically by those against the law and also by those who were positive. Fear of privatization was a dominant argument based on a democratic view where no one should have private ownership.